High‐speed focus‐induced photoresponse in amorphous silicon photodetectors for optical distance measurements. Issue 8 (23rd February 2022) - Bablich, Andreas; Müller, Maurice; Kienitz, Paul; Bornemann, Rainer; Bolívar, Peter Haring
Abstract: The Focus‐Induced Photoresponse (FIP) enables 3D sensing capabilities by evaluating the irradiance dependent non‐linear detector response in defect‐based materials. Since this advantage is intricately associated to a slow response, the electrical bandwidth of previous FIP sensors is limited to a few kHz only. We report the FIP in amorphous silicon pin photodiodes and propose a sensor read out based on a harmonics analyses. We achieve modulation frequencies of 500 kHz and a non‐linear beat frequency detection up to at least 3.5 MHz, surpassing the bandwidth of state‐of‐the‐art architectures by at least a factor of 175. The FIP sensors further achieve signal‐to‐noise ratios of ∼50 dB, depth resolutions of at least 5.4 mm at 126 cm and a DC FIP detection limit of 1.3 µW/mm 2 .